Increased Antimicrobial and Multidrug Resistance Downstream of Wastewater Treatment Plants in an Urban Watershed - Mukherjee, Maitreyee; Laird, Edward; Gentry, Terry J.; Brooks, John P.; Karthikeyan, Raghupathy (Frontiers in Microbiology, 2021)
Development and spread of antimicrobial resistance (AMR) and multidrug resistance (MDR) through propagation of antibiotic resistance genes (ARG) in various environments is a global emerging public health concern. The role of wastewater treatment plants (WWTPs) as hot spots for the dissemination of AMR and MDR has been widely pointed out by the scientific community. In this study, we collected surface water samples from sites upstream and downstream of two WWTP discharge points in an urban watershed in the Bryan-College Station (BCS), Texas area, over a period of nine months. E. coli isolates were tested for resistance to ampicillin, tetracycline, sulfamethoxazole, ciprofloxacin, cephalothin, cefoperazone, gentamycin, and imipenem using the Kirby-Bauer disc diffusion method. Antimicrobial resistant heterotrophic bacteria were cultured on R2A media amended with ampicillin, ciprofloxacin, tetracycline, and sulfamethoxazole for analyzing heterotrophic bacteria capable of growth on antibiotic-containing media. In addition, quantitative real-time polymerase chain reaction (qPCR) method was used to measure eight ARG – tetA, tetW, aacA, ampC, mecA, ermA, blaTEM, and intI1 in the surface water collected at each time point. Significant associations (p < 0.05) were observed between the locations of sampling sites relative to WWTP discharge points and the rate of E. coli isolate resistance to tetracycline, ampicillin, cefoperazone, ciprofloxacin, and sulfamethoxazole together with an increased rate of isolate MDR. The abundance of antibiotic-resistant heterotrophs was significantly greater (p < 0.05) downstream of WWTPs compared to upstream locations for all tested antibiotics. Consistent with the results from the culture-based methods, the concentrations of all ARG were substantially higher in the downstream sites compared to the upstream sites, particularly in the site immediately downstream of the WWTP effluent discharges (except mecA). In addition, the Class I integron (intI1) genes were detected in high amounts at all sites and all sampling points, and were about ∼20 times higher in the downstream sites (2.5 × 107 copies/100 mL surface water) compared to the upstream sites (1.2 × 106 copies/100 mL surface water). Results suggest that the treated WWTP effluent discharges into surface waters can potentially contribute to the occurrence and prevalence of AMR in urban watersheds. In addition to detecting increased ARG in the downstream sites by qPCR, findings from this study also report an increase in viable AMR (HPC) and MDR (E. coli) in these sites. This data will benefit establishment of improved environmental regulations and practices to help manage AMR/MDR and ARG discharges into the environment, and to develop mitigation strategies and effective treatment of wastewater.